Vascularized Bone Grafts from the Dorsal Wrist for the Treatment of Kienböck Disease - Nakagawa, Makoto (J Wrist Surg, 2016)
Purpose The objective of this article is to evaluate functional and radiological outcomes of vascularized bone grafts for stage 2 and 3 Kienböck disease. The outcomes of three different donor sites via dorsal approach of the wrist were compared. Pearls and pitfalls in surgical technique were discussed. Methods There were 28 patients who underwent vascularized bone grafts, including the extensor fourth and fifth compartmental artery graft of distal radius in 8 patients, the first and second supraretinacular intercompartmental artery graft of distal radius in 12 patients, and the second dorsal metacarpal neck graft in 8 patients. Average age was 32 years, and radiological grading according to Lichtman classification was stage 2 in 8 patients, stage 3A in 10 patients, and stage 3B in 10 patients. Temporary pinning fixing the midcarpal joint was conducted for 10 weeks postoperatively. Results Follow-up periods averaged 70 months. Pain reduced in 27 patients, and visual analog scale for pain of pre- and postoperative level averaged 59 and 18. Range of wrist flexion and extension motion improved from 87 to 117 degrees, and average grip strength improved from 21 kg preoperatively to 33 kg postoperatively. Carpal height ratio had almost no change from 0.52 to 0.53. Fragmentation of necrotic bone healed in 7 of the 14 cases. Comparative analyses of functional and radiological outcomes between three donor sites found no significant difference. Conclusion Three different vascularized bone grafts from the dorsal wrist and hand area demonstrated favorable and comparable functional outcomes. It was technically important to elevate vascular bundle with surrounding retinaculum or fascia, to include sufficient periosteum, and to insert the vascularized bone as the cortex aligned longitudinally.